Beyond reforms : structural dynamics and macroeconomic vulnerability - Ocampo, José Antonio (Stanford Univ. P. Palo AltoUS, 2005)
Looks at issues of long-term growth and development patterns. Focuses on issues of macroeconomic vulnerability and its social effects.